Еlectrophysical parameters of the diodes for broadband noise generation - Busliuk, Viktar V.; Neroda, Ilona Y.; Pyatlitski, Aliaksandr N.; Prasalovich, Uladzislau S.; Yankouski, Yuri N. (Journal of the Belarusian State University. Physics, 2017)
The volt-ampere and volt-farad characteristics of silicon diodes – noise generators fabricated by the planar technology for the formation of small diameter (
Keywords: diodes – noise generators; electrophysical parameters; microplasmas